Performance of Indian Indigo (Indigofera tinctoria L.) accessions as intercrop in coconut garden - Sarada, S.; Reghunath, B.R. (Journal of Plantation Crops, 2009)
Thirty accessions of Indian indigo (Indigofera tinctoria L.), collected from inside and outside Kerala, were grown in a coconut plantation so as to identify the superior accessions with respect to leaf yield and indigo dye content. Observations were taken at various growth stages namely pre-flowering (90 DAS), flowering (150 DAS) and seed maturation stages (240 DAS). The best ten accessions that recorded maximum leaf yield and glycoside content, obtained from phase I experiment were selected for the phase II experiment. Considerable variations were not noticed in plant height increment in different accessions during both the phases. The accessions differed significantly with respect to plant spread in both the phases. Among the accessions, those that revealed a trend to dominate in plant spread increment during both the phases were IT-105, IT-108 and IT-114. Accession IT-109 dominated in the increment of number of leaves during phase I experiment. Accessions IT-96, IT-99, IT-101, IT-106 and IT-108 were found superior with respect to shoot fresh weight and dry weight in both the phases of the experiment. IT-96, IT-99 and IT-101 were superior in terms of indigo dye content. The present study has revealed the genetic superiority of IT-96, IT-99 and IT-101 accessions in terms of leaf yield and indigo dye content, when grown as intercrop in coconut plantation.